EAR NOSE AND THROAT INJURIES IN CHILDREN - Khan, Arif Raza; Arif, Saatea (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was carried out to determine types and mechanisms of injuries encountered in Ear, Nose and Throat (ENT) regions of children at two localities of NWFP province of Pakistan. Methods: This study was carried out at ENT departments of DHQ Hospital, Swabi and Khyber Teaching Hospital, Peshawar, Pakistan from June 2001 to June 2003. Children up to age 15 years presenting in emergency with ENT injuries or reporting at OPDs were included in the study. Results: 160 children reported with injuries to ENT in this 2 years period. Most of the injuries were in the nasal region (50%) and nasal bone fracture was the commonest (26%). Fall and trauma during playing were the mode of injuries. In children of less than 5 years, the commonest cause of injury was pointed objects in the mouth while in children between 5-10 years the cause was fall. In children of 10-15 years of age the common causes of injury were road traffic accidents (27%) and fall (23%). Conclusion: It is concluded that injuries of ENT in children are different than in adults. The mechanism of these injuries is also different. Keywords: ENT, Injuries, nasal fracture, children.